Effects of TEOs aerogel particles size of TEOS aerogel on its mesoporous structure and thermal behavior via supercritical drying and high temperature - Ibrahim, Ashraf M.; Chiad, Baha T.; Twej, Wesam A. A.; Mohammed1, Ruaa A. (Iraqi Journal of Science, 2019)
TEOS aerogel a is the most commonly used. a Aerogel has attracted increasing attention from both academic and industries due to its extraordinary performance and potentials. We have systematically studied the relationship between the densification temperature of the synthesis environment of silica aerogels on their resulting morphological, optical and thermal properties. SEM and BET measurements were employed as structural probes to ascertain the structural differences. Lee’s disc apparatus was used for determining the thermal conductivity coefficient. There is a systematic correlation between the annealing temperature and the aerogel surface area, porosity, as well as pore size. The implemented autoclave was able to produce aerogel monolith of surface area reaching to 998.25 g/m2 and low electric conductivity arrive to of 1.17*10-4(s/m), associated with density of 0.047 g/cm3.The calculated thermal conductivities were (0.0063, 0.016 and 0.0053 mW m-1 0 C-1) for pH1, pH7 and pH8 samples respectively. The microstructure observed is categorized into three types, namely, open cellular foam (the substance that is formed by trapping pockets of gas in solid), fractal (the structural features it’s clearly show the hierarchical repetition) and isotropic morphology (visible spectrum scale). The aerogel properties were are remarkably varied. While the influence of annealing temperature the reaction setting has gradually influence on the final aerogel properties, h However, it is obviously requested for achieving desirable optically and nano-featured products.